Correlating shelf carbonate evolutive phases with fluid expulsion episodes in the foredeep (Miocene, northern Apennines, Italy). (January 2017) - Conti, Stefano; Fioroni, Chiara; Fontana, Daniela
Abstract: In the Miocene of the northern Apennines of Italy, evolutionary phases of shallow-water carbonates in wedge-top basins are coeval with methane-rich fluid expulsion episodes in the inner foredeep. We identified four main correlative events, primarily controlled by synsedimentary tectonics, sediment input and climate cooling: 1) a Burdigalian tectonic phase determined the onset of shelfal sedimentation in wedge-top areas and is correlated with an important episode of fluid expulsion in marly sediments of the inner foredeep (Croce di Moggiona seep-carbonates); 2) the decrease of shelfal carbonate production and the increase of detrital input in the Early Langhian correspond with a second important episode of seep-carbonate precipitation in the inner foredeep (Castagno d'Andrea); 3) the demise of the carbonate shelf and the coeval expulsion of methane-rich fluids in the inner foredeep (Vicchio and M. Citerna seep-carbonates) at the Langhian/Serravallian boundary approximate the Mi3b cooling event. The lower temperatures, associated with increased siliciclastic weathering, led to the crisis of shallow-water carbonate production whereas the pressure drop due to the eustatic fall may have triggered the gas-charged fluid expulsion; 4) the tectonic-related uplift of frontal sectors of the wedge-top basin led to the wide erosion of the Burdigalian-Langhian carbonates and caused the precipitation of authigenic seep-carbonates (Deruta seep) both in the slope and the adjacent foredeep. Highlights: We correlate carbonate shelf in wedge-top basin with seep episodes in the foredeep. Seep-carbonates are useful stratigraphic markers and climate-tectonic sensitive proxy. Evolutionary phases of Miocene temperate-type carbonates are outlined. Synsedimentary tectonics control the onset and crisis of carbonate sedimentation. Terrigenous discharge and Mi3b climate cooling favored the drowning of the shelf.